To find the solution to the equation -6x + 9 = 4x + 14, we need to isolate the variable on one side of the equation.
First, let's simplify the equation by combining like terms:
-6x + 9 = 4x + 14
Next, let's move the variable terms to one side of the equation by subtracting 4x from both sides:
-6x - 4x + 9 = 14
Combining like terms on the left side, we have:
-10x + 9 = 14
Next, let's isolate the variable by subtracting 9 from both sides:
-10x + 9 - 9 = 14 - 9
Simplifying the equation further, we have:
-10x = 5
In order to solve for x, we need to divide both sides of the equation by -10:
(-10x)/-10 = 5/-10
Simplifying the equation gives:
x = -1/2
Therefore, the solution to the equation -6x + 9 = 4x + 14 is x = -1/2.
What is the solution to the equation -6x + 9 = 4x+ 14?
1 answer